(untitled) (Annals of Medical Research, 2021)
Aim: The prevalence of Helicobacter Pylori (HP) is up to 90% in developing countries, whereas it is less than 40% in developed countries. This study aims to determine the prevalence of HP in Van city and its region and to investigate the relationship between the presence of HP and the clinical, endoscopic appearanceMaterial and Methods: A total of 367 cases that presented with the dyspeptic complaints to the Gastroenterology outpatient-clinic and underwent upper-gastrointestinal endoscopy and gastric biopsies between July/2017-March/2019 were included in the study. The patients included in the study were divided into three age-groups (1-5 years, 6-10 years, 11-18 years). The clinical complaints, endoscopic findings were recorded in all patients. The relationship between HP positivity and clinical complaints, the endoscopic appearance was analyzed.Results: The presence of HP was found in 234(63.8%) patients. However, the incidence of HP was 63.8% in all patients; it was found 34.6% between 1-5 years, 61.8% between 6-10 years, and 71.2% between 11-18 years, respectively. The duodenal ulcer was found in 8.5%(20/234) of HP positive cases, and 3.5%(5/133) of HP negative cases. In predicting the presence of HP, the ulcer specificity was determined 96%, the sensitivity was 8.5%, the positive predictive value was 80%, and the negative predictive value was found 37.4%Conclusion: HP should be considered in patients with recurrent and chronic abdominal pain. Endoscopic appearance of nodular antral gastritis and the ulcer should suggest HP infection. The high rate of activity and chronicity in HP positive cases indicates the importance of HP eradication therapy.